Signs, intraoperative challenges, and management strategies during cataract surgery secondary to inadvertent intralenticular antivascular endothelial growth factor injection. Issue 4 (October 2015) - Kummelil, Mathew Kurian; Thakkar, Maithil; Kharbanda, Varun; Das, Sudeep; Shetty, Rohit; Shetty, Bhujang K.
Abstract : N/A: We report the case of a 74‐year‐old woman who attended our outpatient department complaining of decreased vision in her right eye. Three years previously, an intravitreal injection (bevacizumab [Avastin]) had been given for diabetic macular edema. Slitlamp examination showed immature cataract. Preoperative anterior segment optical coherence tomography (AS‐OCT) of femtosecond laser–assisted cataract surgery showed a deposit over a potentially compromised posterior lens capsule that was not evident on slitlamp examination. The intraoperative challenges during cataract surgery and the management strategies used for a satisfactory clinical outcome are described. To our knowledge, this is the first report of AS‐OCT performed during femtosecond laser–assisted cataract surgery detecting a potentially compromised posterior lens capsule after intravitreal injection. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.